Improvement of freeze-thaw stability of oil-in-water emulsions prepared with modified soy protein isolates. (March 2019) - Zang, Xiaodan; Yue, Chonghui; Liu, Mujun; Zheng, Huanyu; Xia, Xiufang; Yu, Guoping
Abstract: To investigate the freeze–thaw stability of oil-in-water emulsions, we prepared soy protein isolate (SPI), SPI was enzymatically hydrolyzed by papain or by a mixture of papain and phytase, and one cycle or three cycles of freeze–thawing were performed. Their stabilities were assessed by zeta potential, particle size, microstructure, oiling off, and creaming index measurements and the structural changes were characterized by circular dichroism spectroscopy. For emulsions prepared with modified SPI samples, the freeze–thaw stability improved with increasing degree of hydrolysis, especially when the combined enzymatic treatment was performed. Furthermore, the effects of a variety of environmental factors, such as NaCl concentration, pH, and the number of freeze–thaw cycles, were considered with respect to freeze–thaw stability. Emulsions prepared with the most extensively hydrolyzed samples by papain and combined enzymatic treatment, showed a higher freeze–thaw stability than those stabilized by the SPI. In conclusion, SPI modified by papain and phytase treatment can significantly improve freeze–thaw stability and can withstand several environmental factors. The results show promise for supporting the use of SPI as an emulsifier in the food industry. Highlights: Limited hydrolysis of soy protein isolates (SPI) could improve its freeze-thaw stability. The SPI hydrolysis with papain or with papain and phytase mixed was investigated. SPI, DH, P-DH were used to stabilize oil-in-water emulsions. P-DH can improve freeze-thaw stability and withstand several environmental factors.